Pengaruh Kombinasi Tehnik Relaksasi Pernapasan dan Inhalasi Aromaterapi (Chamomile) Terhadap Penurunan Intensitas Nyeri Pada Persalinan Kala 1 - Amalia Indah Puspitasari; Tohiriah Tohiriah (Jurnal Ners, 2025)
Labor is often accompanied by intense pain, especially during the first stage of labor (opening phase). The pain felt during labor can interfere with the mother's comfort and affect the overall labor experience. The government and health workers have several efforts to reduce or manage labor pain, either through medical, psychological, or social approaches. The non-pharmacological approach is done naturally without the use of chemical drugs, one of which is by doing relaxation techniques that include breath relaxation and aromatherapy. Chamomile contains several substances that are beneficial for health. The main content in chamomile such as apigenin, luteolin, chamfer and tannins which have anti-inflammatory, antioxidant, anti-bacterial properties and reduce stress due to contraction pain. The purpose of this study was to determine the effect of a combination of breathing relaxation techniques and chamomile aromatherapy inhalation on reducing pain intensity in labor phase 1.This research method uses descriptive analytic pre-experiment research with pretest postest non-equivalent group design. Data collection was carried out from November 2024 to January 2025. The population was laboring mothers at stage I with total sampling technique, so the number of samples was 30 respondents. The statistical test performed was the T-Test test.The results of statistical tests obtained before being given the action of the majority of respondents' pain intensity in the severe pain category as many as 18 (60%) with an average value of 3.60 and after being given the action the majority became moderate pain as many as 11 (36.7%) with an average value of 2.03. The ρ-value result is 0.009 (p <0.05) so that there is a significant difference, and it can be concluded that there is an effect on the level of pain before and after the combination of Breathing Relaxation Techniques and Chamomile Aromatherapy Inhalation at TPMB Bdn. Winda Widianty Sodikin S.Keb.